2005
DOI: 10.1172/jci200522477
|View full text |Cite
|
Sign up to set email alerts
|

Folate pathway gene expression differs in subtypes of acute lymphoblastic leukemia and influences methotrexate pharmacodynamics

Abstract: The ability of leukemia cells to accumulate methotrexate polyglutamate (MTXPG) is an important determinant of the antileukemic effects of methotrexate (MTX). We measured in vivo MTXPG accumulation in leukemia cells from 101 children with acute lymphoblastic leukemia (ALL) and established that B-lineage ALL with either TEL-AML1 or E2A-PBX1 gene fusion, or T-lineage ALL, accumulates significantly lower MTXPG compared with B-lineage ALL without these genetic abnormalities or compared with hyperdiploid (fewer than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…Thus, to improve further the outcome of pediatric ALL, it is necessary to apply fusion gene or subtype‐specific treatment protocols, or combine the current chemotherapy regimens with new target drugs. Two reports from St. Jude Children's Research Hospital indicated that TEL‐AML1 + patients should be treated with intensive asparaginase and high‐dose methotrexate [45, 46]. Imatinib has been reported to enhance the 3‐year EFS rate of BCR‐ABL + ALL to 80% [47] significantly, which is twice the rate achieved before imatinib was used.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to improve further the outcome of pediatric ALL, it is necessary to apply fusion gene or subtype‐specific treatment protocols, or combine the current chemotherapy regimens with new target drugs. Two reports from St. Jude Children's Research Hospital indicated that TEL‐AML1 + patients should be treated with intensive asparaginase and high‐dose methotrexate [45, 46]. Imatinib has been reported to enhance the 3‐year EFS rate of BCR‐ABL + ALL to 80% [47] significantly, which is twice the rate achieved before imatinib was used.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical characteristics (age, phenotype, presenting WBC count, and cytogenetics) may soon give way to molecular diagnostics related to differences in relative gene expression or presence of single nucleotide polymorphisms. Among patients with ALL [Kager et al, 2005;Pui and Evans, 2006] or rheumatoid arthritis [Dervieux et al, 2004[Dervieux et al, , 2005 treated with MTX, for example, patterns of gene expression or of polymorphisms within genes relevant to (anti)folate metabolism have been used to distinguish subsets of patients with dissimilar risks of treatment response or toxicity. It is reasonable to expect that this approach will identify patient subsets at higher than average risk of delayed neurotoxicity.…”
Section: Predictors Of Adverse Neurocognitive Outcomesmentioning
confidence: 99%
“…For example, Zaza et al 41 showed that several genes involved in purine metabolism were differentially expressed (lower) in the TEL-AML1 ALL subtype and this subtype had lower DNPS activity. In addition, this subtype had lower MTXPG accumulation ( Figure 3) and Kager et al 31 described how genes involved in folate transport, metabolism, and polyglutamylation were differentially expressed in different ALL subtypes, including TEL-AML1 (Figure 2). Data from these results can help validate folate pathway model simulations and help develop and test hypotheses on why TEL-AML1 ALL has a favorable prognosis.…”
Section: Drug Sensitivity and Resistancementioning
confidence: 92%
“…The use of this approach has the potential to yield a more robust and complete understanding of how sensitive the system is to biologically plausible perturbations such as those resulting from polymorphisms in folate pathway genes. 7,30 An example of the correlation structure of folate-related gene expression is described by Kager et al 31 They showed that the expression levels of DHFR, TYMS, MTHFD1, MTHFD2, ATIC, GART, and RUVBL2 are strongly correlated with each other. This suggests an appropriate approach to investigating the sensitivity of the model is to vary this group of enzymes (parameters) in the same correlated manner.…”
Section: Model Parameter Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation